Harmonizing Language Acquisition: Exploring the Link between English Song Listening Frequency and Vocabulary Proficiency - Michael Belo; Darmawan; Abdul Gani, Hastini (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
Students need to have a wide range of vocabulary to communicate effectively. However, many students face vocabulary-related problems such as a lack of vocabulary and difficulty in identifying word meanings. One of method that can help improve students' vocabulary is to listen to English songs repeatedly and acquire vocabulary through the lyrics of the songs. This study was conducted at SMAN 6 Sigi with a sample size of 90 students. This research is quantitative research with correlational method. The researchers collected data using interview and test. The Pearson Product Moment result of both data analysis instruments is 0.011. The category is neligible. This indicates that there is no relationship between both variables. There are several factors identified as the cause of no correlation; first, the context of the vocabulary measurement instrument is not relevant to the frequency listening instrument. Second is the low motivation of students to learn English through songs, as only about 29% of students have motivation to learn English through songs. Third, the listener's experience with English and the frequency of listening to English songs. Fourth is the student's time preference when listening to English songs. And the last factor is the music preferences of each student. Keywords: Correlation; Listening to English Song; Vocabulary